Advanced Compressor Loss Correlations, Part II: Experimental Verifications - M. T. Schobeiri (International Journal of Rotating Machinery)
Reliable efficiency calculation of high-subsonic and transonic compressor stages requires a detailed and accurate prediction of the flow field within these stages. Despite the tremendous progress in turbomachinery computational fluid mechanics, the compressor designer still uses different loss correlations to estimate the total pressure losses and thus the efficiency of the compressor stage. The new shock loss model and the modified diffusion factor, developed in Part I, were implemented into a loss calculation procedure. In this part, correlations for total pressure loss, profile loss, and secondary loss coefficients are presented, using the available experimental data. Based on the profile loss coefficients, correlations were also established for boundary layer momentum thickness. These correlations allow the compressor designer to accurately estimate the blade losses and therefore the stage efficiency.